Implementasi Balai Monitor Spektrum Frekuensi Radio Kelas 1 Medan Dalam Upaya Mengatur Pelayanan Jaringan Radio - Miftahul Jannah Hasibuan; Nur Ahmadi Bi Rahmani (Jurnal Riset dan Inovasi Manajemen, 2023)
Radio monitoring is a way of regulating the use of radio frequency spectrum by broadcasting media in the territory of the Unitary State of the Republic of Indonesia, this is regulated by the Directorate of Resources and Equipment of Post and Technology Data (Ditjen SDPPI) which is responsible for carrying out the functions of regulating, supervising and controlling the frequency spectrum using radio monitoring to monitor, observe, and control the use of frequency spectrum by broadcasting media in the territory of the Unitary State of the Republic of Indonesia. The purpose of this study was to find out how the implementation of Class 1 Medan's Class 1 Radio Frequency Spectrum Monitoring Center in an effort to regulate radio services. This research is a qualitative research that is descriptive in nature, namely describing and explaining the problem according to the facts in the field.